The expansion of global LNG trade and its implications for CH4 emissions mitigation - SiJia Gao; GuoSheng Zhang; ChengHe Guan; HaoRan Mao; Bo Zhang; He Liu (Environmental Research Letters, 2023)
In recent years, the global trade in liquefied natural gas (LNG) has experienced significant growth, leading to a rise in the effect of embodied methane (CH _4 ) emissions between economies. This study investigates the spatiotemporal evolution of these CH _4 emissions embodied within the global LNG trade and examines the associated network characteristics between the years 2011 and 2021. The findings reveal a substantial increase of 43.3% CH _4 emissions embodied in global LNG trade, reaching a peak of 2.75 Tg in 2021, which equates to a monetary value exceeding 5 billion USD in terms of natural gas. Over the study period, these emissions aggregated to a total of 1987.92 Mt CO _2 -eq and 718.06 Mt CO _2 -eq, based on the respective global warming potential values over 20 year and 100 year timeframes. Our investigation of this complex network reveals the emergence of multiple robust hub economies, which have exerted significant influence over the dynamics of supply-demand in embodied CH _4 trade, as well as the structure of trade communities. Notably, the Asia-Pacific trading community has exhibited exceptional growth and prominence in this market. Such growth is directly related to an increase in embodied CH _4 emissions and their overall standing within this community’s network. The US has steadily attained dominance within an export-oriented community, which encompasses economies in South and North America, as well as certain regions of Europe. Moreover, the redistribution of LNG-related CH _4 emissions among economies is significantly impacted by the intensity of production emissions and the volume of LNG trade. This reveals the potential of these hub economies to drive substantial reductions in CH _4 emissions by implementing targeted energy and climate policies, which they have launched. Reinforcing coalitions and fostering closer collaboration within these communities can provide a robust foundation for technological advancements and transformative changes in trade structures.